Pengembangan Modul Rekam Medis Elektronik (RME) Rehabilitasi Medik Rawat Jalan - Jayanti, Asykar; Sugiarsi, Sri; Rohmadi, Rohmadi (Politeknik Negeri Jember, 2024)
The outpatient medical record documentation at RSUP dr. Soeradji Tirtonegoro already uses Electronic Medical Records (EMR), except for the Medical Rehabilitation clinic. This results in patient medical records data not being integrated into the EMR, requiring consulting doctors to access physical medical record files to view notes from the Medical Rehabilitation clinic. The aim of this research is to develop an electronic medical record system for outpatient medical rehabilitation. The research method used is Research and Development (R&D), with system development employing the Rapid Application Development (RAD) method. The outcome of this research is an electronic medical record module for outpatient medical rehabilitation, used by nurses, doctors, and therapists visiting the Medical Rehabilitation clinic to document patient records. It is recommended for future researchers to add a patient initial assessment module for nurses and doctors. It is also hoped that this system can be integrated with the billing system and digital claims, enabling the information system to be fully utilized in the services provided at the Medical Rehabilitation clinic.